Realization of the Benefits and Determinants of Information Systems Strategic Planning for Higher Educations in Indonesia using Systematic Literature Review. - Bernadus, Gunawan Sudarsono; Sri, Poedji Lestari; Alexius, Ulan Bani; Aedah, Abd Rahman (2020)
Research related to information systems strategic planning (ISSP) continues to this day. Likewise ISSP research at Higher Educations in Indonesia. ISSP is an information system planning concept that is very important in the information system development life cycle. ISSP provides the realization of benefits, which are obtained from the determining factors. ISSP research results currently have a lot to discuss the realization of benefits and its determinants, but not much explored the accumulation of benefits and their determinants in a certain period. This exploration activity is important to obtain the reality and phenomenon of the actual use of ISSP to support the right determination for the organization, especially related to determining the realization of benefits and their determining factors. The purpose of this study is to explore the realization of the benefits of ISSP and its determinants in Indonesian Higher Educations in the period 2009 to 2019 using the method of systematic literature review (SLR). The results of this study are in the form of a synthesis of ISSP benefit realization and its determinants.